Pactum De Compromittendo In Shares Purchase Agreement - Iswari, Benny; Ansari , Teuku Syahrul; Victor, Indra Yudha Victor; Hadipura, Margo Hadipura (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
The parties, namely the Seller and the Buyer have agreed to determine the arbitration clause in the form of a pactum de compromittendo made in writing and incorporated into the deed of the principal agreement for the sale and purchase of shares of PT. Indonesian Rice Granary. This means that since the beginning before the occurrence of a dispute, the choice of settlement has been determined through the Indonesian National Arbitration Board. In 2021, the Seller files a lawsuit against the Buyer as the Defendant through the general court to request that the said share sale and purchase agreement be declared null and void and has no binding force. In their decision, the Panel of Judges stated that in essence the Central Jakarta District Court had no authority to try this case. Regarding the legal considerations, the assembly based the rules in Article 118 HIR and Article 3 of Law no. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. This study uses a normative juridical approach with the results of the research showing that the enforceability of an arbitration clause in the form of a pactum de compromittendo is binding on the parties according to the pacta sunt servanda principle contained in Article 1338 Paragraph (1) of the Civil Code and the judge's decision as in its considerations is correct and has been according to law.